Laparoscopy in acute abdomen between encouragement and inhibition - Helmy, Mena Zarif; Aldardeer, Ahmed Abdel Kahaar (International Surgery Journal, 2019)
Background: Laparoscopy has been a valuable technique in the treatment of acute abdominal diseases and can be considered either to diagnose or to treat selected cases. Methods: Here, we randomly select patients with acute abdominal pain in whom the diagnosis was not clear after ultrasonography and plain X-ray, we did diagnostic laparoscopy and according to its findings, we proceeded to surgical intervention. 50 cases with acute abdomen were included in this study in order to clarify the role of laparoscopy in the diagnosis and treatment of acute abdomen. Results: From the 50 patients, the main complaint was abdominal pain and presented in (100%) of patients, 38 of patients had vomiting, fever in 29 patients and 14 patients had abdominal distension, 7 patients had alteration in bowel habits and burning micturition in 6 patients. In this study, 10 patients had past history of previous surgery. By laparoscopy we could see the pathology in 46 patients and complete the management in all of patients but failed to reach the diagnosis in 2 cases and conversion to laparotomy in other 2 cases. Laparoscopic surgery mean was 47.9±12.4 minutes. Hospital stay mean was (1.851) days. Morbidity was 10%. No mortality was found in our study. Conclusions: Laparoscopy can be considered safe for diagnosis and effective in the treatment of patients with acute abdomen. It may be useful to avoid the unnecessary laparotomies in a large number of patients presented with acute abdominal pain.